Minimally Invasive Plate Osteosynthesis for a Distal Radius Fracture with Forearm Skin Problem - Kiyohito Naito; Yoichi Sugiyama; Mayuko Kinoshita; Ahmed Zemirline; Chihab Taleb; Thitinut Dilokhuttakarn; Philippe Liverneaux; Kazuo Kaneko (Case Reports in Orthopedics)
In this study, we performed osteosynthesis for a distal radius fracture using a minimally invasive approach for a patient with skin disorder of the forearm and obtained favorable results. This case report may provide new findings confirming the usefulness of this surgical approach for distal radius fractures. Blister formation on the right forearm was observed in a 53-year-old female who was diagnosed with a distal fracture of the right radius and underwent splinting in a local hospital, and she was referred to our hospital 2 days after the injury. Minimally invasive locking plate osteosynthesis was performed, and there was no skin lesion at this incision site. Postoperatively, there were no complications in soft tissues and the operative scar was almost unrecognizable. We reported volar locking plate osteosynthesis using the minimally invasive approach in a patient with skin disorder of the forearm. Such patients are rarely encountered. However, this minimally invasive approach is extremely useful for utilizing the advantages of volar locking plate fixation without being affected by the soft tissue environment.